Exploring the critical success factors for the financing of public-private partnerships in the roads and transport sector: a case study of Gauteng province. - Mudau, Lufuno (Graduate School of Business (GSB), 2023)
This research study identified the critical success factors for financing Public-Private Partnership (PPP) projects in the roads and transport sector at the provincial level in South Africa, with the aim of giving policy makers, academics and practitioners a glimpse of the existing conditions prevalent in the financing of PPPs. Transport and rail infrastructure are critical for trade as they contribute to the enhancement of inter-African trade initiatives and agreements. This study employed a thematic analytic approach to identify the critical success factors of financing PPPs within Gauteng province using four case studies, three of which were toll road concessions and the other a rail transport PPP. Overall, nine participants were interviewed from the public (project owners) and private sectors (concessionaire), with two participants coming from academia and National Treasury. The findings on the critical success factors of financing transport infrastructure are consistent with international best practice. Specifically, the success factors identified include available financial markets, experienced and skilled private sector consortiums, value for money, government support, effective and efficient procurement processes, learning from others' experience, PPP finance structure and risk allocation. The study's recommendations are that the public sector should select the best team for the job by ensuring that they select a private consortium with the necessary skills and experience. They also suggest that the public sector should be involved in the negotiation of funding, even in instances where the private partner is providing 100% of the capital funding. Another critical recommendation is to secure investment in training and development by the regulator, as this will ensure that the private and public sector officials involved in infrastructure development are well-versed on the legislative requirements and processes that are to be followed to successfully execute PPP projects. Procurement processes should also remain fair and competitive in all stages of the project development, including the operational phase. Lastly, in order to curb community protests, all relevant spheres of government should be actively involved to address the root causes of such protests